Pengembangan Strategi Pembelajaran Berlandaskan Cara Berpikir Kreatif untuk Membuat Karya Arsitektur - Happy Indra Dewi (JTP - Jurnal Teknologi Pendidikan, 2015)
Development Strategy Based Instructional Creative Thinking for Making Architecture Work. The research on the development of instructional strategies based on creative thinking to help students beginners to transform ideas into architectural works efficiently and effectively in the course Architectural Studio 1. Methods of research to develop and validate a product using the Research and Development of Borg and Gall. The results of the study are creative instructional strategies, which collaborate brain thinking, facilitate creative thinking methods (mind map, biodrawing, study 3-dimensional) and the concept transformatik (formula of Lie Tjun Tjie) to produce new findings. Test feasibility testing through expert (instructional design, creative architecture and media) and to determine the effectiveness of the test to the students of Department of Architecture, known creative instructional strategy has proved feasible and effective for subjects Architecture Studio 1